Water level effect on herbaceous plant assemblages at an artificial reservoir-Lago Azul State Park, Southern Brazil - Souza,D. C. (2015)
This study presents the effect of water level variation on the assemblages of herbaceous species in Mourão I Reservoir, Lago Azul State Park, Southern Brazil. The structure and distribution of populations was examined in February (dry period) and April (rainy period), 2011, in two transects. These transects started at the forest edge towards the center of the lake. The end of the transect coincided with the end of the plants within the lake. On every two meters along of the transects we sampled a wooden square of 0.25 m2 for species biomass analysis.The macrophyte stand was composed entirely of emergent species. Considering the periods, most species were less frequent in the rainy period (April), but Ipomea ramosissima (Poir.) Choisy, Commelina nudiflora L., Eleocharis acuntagula (Roxb.) Schult. and Verbena litorales (Kunth.) had their frequency increased during this period, probably due to their resistance. The influence of flood as measured by the NMDS point out that both before and after the flood, there are plots with distinct compositions and biomass. The water level variation affects the dynamics of plant composition and structure in marginal areas of the Reservoir.